Genetic control of grain protein content and of agronomic traits in maize cultivated at different levels of nitrogen fertilization - Bueno, Luíce Gomes; Chaves, Lázaro José; Oliveira, Jaison Pereira de; Brasil, Edward Madureira; Reis, Américo José dos Santos; Assunção, Aracelle; Pereira, André Ferreira; Ramos, Michele Ribeiro (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to determine the genetic control of grain protein content and of the agronomic traits of corn (Zea mays) at different levels of nitrogen fertilization. Nine parent populations and their hybrids were evaluated in a complete diallel mating design, with two levels of nitrogen fertilization. The variables evaluated were: relative chlorophyll index, plant height, ear height, ear production, grain yield, grain color, mass of 100 grains, density of grains, nitrogen content in the leaves and grain protein content. Increasing levels of nitrogen fertilization increased the relative chlorophyll index, ear height and grain protein content. However, only grain production had distinct genetic control at different levels of nitrogen. Diallel analysis showed significant genotype effect in all traits, except for grain and ear production. For most of the variables, there was significance of heterosis effect. For grain protein content, there was no significance for specific combining ability, and genotypes general combining ability had more important effects in the expression of this character.